Management of Service Quality Improvement in Junior High Schools: A Total Quality Management (TQM) Perspective - Yogi Listiana (EDUJAVARE: International Journal of Educational Research, 2026)
Management of Service Quality Improvement in Junior High Schools: A Total Quality Management (TQM) Perspective